Pengaruh Pelatihan Pelayanan Kefarmasian terhadap Pengetahuan Pengelola Obat di Puskesmas Kabupaten Ogan Komering Ilir - Hafizh Amrullah; Satibi Satibi; Achmad Fudholi (Faculty of Pharmacy, Universitas Gadjah Mada)
The increasing number of patients admited to primary healthcare (PHC) in the JKN era demands the readiness of PHC’s staff, especially pharmaceutical staff, to serve the community. Knowledge is a major necessity in collaborating with other health profesional to improve the quality of health services. Pharmaceutical staff who lack knowledge needs special training to improve their competences in drug management and clinical pharmacy services. This study aims to determine the effect of pharmacy service training on the knowledge of drug manager in PHC’s of Ogan Komering Ilir district. This research is a quasi-experimental design research with pre and post analysis approach in the intervention group and using the control group as a comparison. Subjects in the study were drug managers in the PHC’s of Ogan Komering Ilir district that met the criteria. The intervention was carried out by providing training to drug manager and providing pharmacy service manuals. The training material provided was based on the Pharmaceutical Services Training Curriculum compiled by Ministry of Health. Another instrument used was a validated questionnaire to measure the knowledge score of drug managers before and after training. A total of 13 drug managers participated in this study. After the training, the knowledge score of drug manager in the intervention group increased from 9.83 ± 2.401 to 12.67 ± 2.333 with value of p = 0.013. The majority of intervention group drug managers experienced an increase in knowledge both from the aspect of drug management and clinical pharmacy service aspects. This study concludes that training of drug managers has an effect on increasing knowledge of aspects of drug management and clinical pharmacy services.